BIOSTRATIGRAPHIC CHARACTERISTIC OF STAGE STRATOTYPES OF THE PERMIAN SYSTEM - Chuvashov B.I.; Chernykh V.V.; Bogoslovskaya M.F. (My University, 2002)
Stratotype sections of the Asselian, Sakmarian, Artinskian, and Kungurian stages of the Cisuralian Series of the Permian System, which were studied to meet requirements of the International GSSP project, are considered. The complex paleontological substantiation of lower boundaries is presented for all stages, and their stratotypes and parastratotypes are indicated. In the Aidaralash stratotype section (western Kazakhstan), the lower boundary of the Asselian Stage that coincides with the Carboniferous-Permian boundary is placed at the base of the Sphaeroschawagerina vilgaris (fusulinids) and Streptognathodus isolatus (conodonts) zones and separates the ammonoid Shumardites-Vidrioceras and Svetlanoceras-Juresanites genus-zones. In the Kondurovka stratotype section located at the Sakmara River (Orenburg region), the lower boundary of the Sakmarian Stage is proposed to be at the first occurrence level of Sweetognathus aff. merrilli (conodonts) and Pseudofusulina moelleri (fusulinids); ammonoids do not occur at this level. The Kondurovka section is proposed to be the lower boundary stratotype of the Artinskian Stage, as the boundary marks here the first occurrence level of fusulinid assemblage characteristic of the Pseudofusulina pedissequa-Pseudofusulina concavatus Zone, Artinskian ammonoids, and conodonts of the whitei Zone. The base of the Kungurian Stage corresponding to the lower boundary of the Sarana Horizon is established in the Mechetlino stratotype section, using the Neostreptognathodus pequopensis-Neostreptognathodus pnevi phylogenetic lineage of conodonts.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская